1995
DOI: 10.3109/02656739509052340
|View full text |Cite
|
Sign up to set email alerts
|

Cell killing, DNA polymerase inactivation and radiosensitization to low dose rate irradiation by mild hyperthermia in four human cell lines

Abstract: Four human cell lines (one fibroblast, two melanoma and one glioma) were evaluated for their responses to hyperthermia and thermalradiosensitization. For mild hyperthermia (40-42 degrees C), there was little to no chronic thermotolerance development during protracted heating for up to 72 h. In addition, there was no significant thermotolerance for polymerase inactivation during mild hyperthermia. For high temperature hyperthermia, polymerase beta was more thermal sensitive than aphidicolin sensitive polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Earlier studies have shown that there were di erences in the relative responses of polymerase and polymerase ¬ ‡¯ ‡ " to hyperthermia at 41 and 458C. Polymerase activity was much more inhibited at 458C than polymerase ¬ ‡¯ ‡ ", while at 418C the opposite was true 14,36 . Thus, the absence of polymerase could simply represent the absence of a target for high temperature heating, while for low temperature heating this may not be as critical.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have shown that there were di erences in the relative responses of polymerase and polymerase ¬ ‡¯ ‡ " to hyperthermia at 41 and 458C. Polymerase activity was much more inhibited at 458C than polymerase ¬ ‡¯ ‡ ", while at 418C the opposite was true 14,36 . Thus, the absence of polymerase could simply represent the absence of a target for high temperature heating, while for low temperature heating this may not be as critical.…”
Section: Discussionmentioning
confidence: 92%
“…A novel finding of this study is that the human melanoma cells develop thermotolerance during heating at 42 C. There are several reports that human cells, unlike rodent cells, do not develop chronic thermotolerance during mild hyperthermia [35][36][37] . Two melanoma cells lines previously studied, SK-Mel-3 and HT144, did not develop chronic thermotolerance during 42 C 37 .…”
Section: Discussionmentioning
confidence: 97%
“…Whilst, earlier studies showed that mild hyperthermia initially increased DNA double-strand break repair 2,34 , our studies have shown that under conditions of long-duration mild hyperthermia, there was a good correlation between radiosensitization and the increased number of DNA strand breaks 35 . While earlier studies demonstrated a good correlation between thermoradiosensitization and DNA polymerase inactivation [36][37][38][39] , note that at mild hyperthermia temperatures there was an increase in DNA polymerase activity, but the activity of the polymerase group þ þ " was more sensitive to LDMH 40 . Recent results have now indicated that polymerase may not be involved in thermoradiosensitization 41 .…”
Section: Mechanisms Of Thermoradiosensitizationmentioning
confidence: 93%